Performance Driven Six-Port Receiver and Its Advantages over Low-IF Receiver Architecture - Abul Hasan; Mohamed Helaoui (Journal of Electrical and Computer Engineering)
This paper provides an extensive analysis of the performance of a six-port based direct conversion receiver (SPR) in terms of signal quality, dynamic range, noise figure, ports matching, isolation, bandwidth, and cost. Calibration technique using multimemory polynomials has been adopted in order to improve the signal quality of the six-port receiver. The performances of the calibrated receiver are then compared with the performances of a commercially available I-Q demodulator used as a low-IF receiver. The main advantages and disadvantages of the SPR compared to the low-IF receiver are highlighted. The major advantages of the SPR come in terms of its available input frequency bandwidth and the low power requirement. The SPR system requires no external bias supply but suffers in terms of the available conversion gain. A better port matching of the SPR can be guaranteed over a wide frequency bandwidth, which mixer based receiver systems lack. The main component limiting the performance of a SPR is the diode detector. A faster and a better diode detector will alleviate some of the problems highlighted in this paper. The SPR system is calibratable and its error-vector-magnitude performance can be made better than the I-Q demodulator used as a low-IF receiver.